PENAPISAN DAN KARAKTERISASI BAKTERI TERMOFILIK DARI SUMBER AIR PANAS SAPAN, KABUPATEN SOLOK SELATAN SEBAGAI PENGHASIL ENZIM TERMOSTABIL PROTEASE - Muqarramah, Mufidhatul; Agustien, Anthoni; Alamsjah, Feskaharny (Universitas Jambi, 2026)
Thermostable protease enzymes can be produced by thermophilic bacteria that act as biocatalysts in protein hydrolysis and have extensive industrial applications. The supply of stable and high-performance protease enzymes is still insufficient, encouraging exploration of thermophilic bacteria from extreme environments as potential producers. The aim of this study was to identify and characterize the macroscopic, microscopic, physiological, and biochemical features of thermophilic bacterial isolates that indicated protease production. This study was conducted using descriptive methods through rejuvenation, screening, and characterization of thermophilic bacteria isolated from the Sapan Hot Spring, South Solok Regency, as potential thermostable protease producers. Based on the results, six protease-producing thermophilic bacterial isolates, namely TUA-01, TUA-02, TUA-11, TUA-21, TUA-26, and TUA-31, with the highest Proteolytic Index (PI) value being isolate TUA-26. Characterization of the six protease-producing thermophilic bacterial isolates revealed differences in colony morphology characteristics, Gram-positive, rod-shaped cells, subterminal spores, motility, and catalase-positive. The thermophilic bacterial isolate TUA-26 has the potential to produce thermostable protease enzymes at high temperatures, making it highly promising for use in various biotechnology and industrial applications.